Top-down silicon microcantilever with coupled bottom-up silicon nanowire for enhanced mass resolution. (18th March 2015) - Vidal-Álvarez, Gabriel; Agustí, Jordi; Torres, Francesc; Abadal, Gabriel; Barniol, Núria; Llobet, Jordi; Sansa, Marc; Fernández-Regúlez, Marta; Pérez-Murano, Francesc; San Paulo, Álvaro; Gottlieb, Oded
Abstract: A stepped cantilever composed of a bottom-up silicon nanowire coupled to a top-down silicon microcantilever electrostatically actuated and with capacitive or optical readout is fabricated and analyzed, both theoretically and experimentally, for mass sensing applications. The mass sensitivity at the nanowire free end and the frequency resolution considering thermomechanical noise are computed for different nanowire dimensions. The results obtained show that the coupled structure presents a very good mass sensitivity thanks to the nanowire, where the mass depositions take place, while also presenting a very good frequency resolution due to the microcantilever, where the transduction is carried out. A two-fold improvement in mass sensitivity with respect to that of the microcantilever standalone is experimentally demonstrated, and at least an order-of-magnitude improvement is theoretically predicted, only changing the nanowire length. Very close frequency resolutions are experimentally measured and theoretically predicted for a standalone microcantilever and for a microcantilever-nanowire coupled system. Thus, an improvement in mass sensing resolution of the microcantilever-nanowire stepped cantilever is demonstrated with respect to that of the microcantilever standalone.